PERAN MEDIA SOSIAL PADA PERILAKU FOMO DRAMA KOREA OLEH GEN Z - Siti Nurhaliza; Fadila Anjani; Rauly Sijabat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Fear of Missing Out (FoMO) is a social anxiety that arises when a person feels left behind from trends or experiences that are considered important by their social environment. In addition, among Gen Z (Generation Z), FoMO is often associated with high social media usage, especially in the context of entertainment such as Korean dramas. The purpose of this study is to determine the role of social media in causing FoMO behavior of Korean dramas by Gen Z. This study uses qualitative research methodology with data collection techniques through interview methods. The triangulation used in this research is methodological triangulation and data triangulation. From the results of this study, it can be concluded that social media plays a major role in shaping FoMO in Gen Z in shaping the decision to watch Korean dramas.